Towards Ultrafast Laser Micromachining of X-Ray Gratings and Creation of Sub-Micron Hole Patterns, Comparison of Results With Bessel and Gaussian Beams - Carreto, Romain; Lüscher, Beat; Holtz, Ronald; Resan, Bojan (Frontiers in Physics, 2022)
We compare micromachining results with Gaussian and Bessel beams using an UV picosecond laser system and demonstrate feasibility to produce tungsten gratings for x-ray interferometry medical imaging, and sub-micrometer size hole patterns. The advantages of Bessel beams compared to Gaussian beams, are demonstrated for micromachining of rectangular shallow profile gratings with sharp edges. The high-aspect ratio grating (10 microns wide and 200 microns deep) from tungsten foil could only be obtained with the Gaussian beam and focusing with an F-Theta type lens. Bessel beams contain significant amount of energy in the side lobes in comparison with the central peak. The limited amount of the pulse energy in the central, 2-micron peak of the beam and destruction of the Bessel beam structure due to the narrow slit clipping the side lobes, prevented the Bessel beam deeper penetration. On the other hand, the axicon lens and the Bessel beam shape enable creation of shallow sub-micron size structures.